RESEARCH OF THE POSSIBILITY OF USING VEGETABLE FILLERS IN THE PRODUCTION OF GRANULATED COTTAGE CHEESE - K. N. Laricheva; A. S. Petrova; M. V. Osipova; E. P. Suchkova (Новые технологии, 2020)
The article shows the feasibility of using vegetable fillers in the production of granulated cottage cheese. The theoretical and experimental substantiation has been given. The possibility of using vegetable fillers in the production of granulated cottage cheese has been investigated. The objects of the study are: grained cottage cheese; «Half-sour dill pickles» vegetable filler; sample tests of cottage cheese with vegetable filler «Half-sour dill cucumbers»; control sample without the filler. Production of the studied samples was carried out in accordance with the TI TC following the generally accepted technology for the production of grained cottage cheese. Organoleptic and physical and chemical evaluation of experimental samples has been carried out in accordance with the established requirements of the standards.As part of the research, technological compatibility of the «Half-sour dill pickles» vegetable filler and cottage cheese has been studied, the effect of vegetable fillers on the organoleptic and physical and chemical characteristics of the finished product has been shown.The optimal ratio of the main ingredients in the formulation has been experimentally revealed. The optimal formulation has been calculated and the technology for the production of a new product developed. The results of the study indicate that the developed product meets the requirements of regulatory and technical documentation and can be recommended as dietary and sport nutrition due to its physical and chemical, organoleptic and  microbiological indicators.